Factors Influencing Visitors Willingness to Pay at Situtirtamarta Nature Tourism - Ira Dzatini; Sodik Dwi Purnomo; Bagus Adhitya (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Although willingness to pay (WTP) has been widely examined in tourism research, empirical evidence regarding the factors influencing visitors’ WTP at the Situtirtamarta Nature Tourism Destination in Purbalingga Regency remains limited. This study analyzed the determinants of visitors’ WTP at the destination. A quantitative approach with a survey design was employed, involving 100 respondents selected through purposive sampling. Data were collected using a structured questionnaire and analyzed through binary logistic regression to assess the effects of ten independent variables on the probability of visitors’ willingness to pay. The findings demonstrated that the regression model was statistically significant overall. Partially, travel cost, length of visit, occupation, income level, and visit frequency significantly influenced visitors’ WTP, whereas gender, age, years of education, marital status, and number of dependents had no significant effects. These results indicate that visitors’ WTP is primarily shaped by economic conditions and visit-related characteristics rather than demographic factors. This study extends the tourism economics literature by providing empirical evidence on the determinants of WTP in a nature-based tourism context. The findings also provide practical implications for tourism managers and local governments in developing appropriate admission-pricing policies, improving service quality, and supporting the sustainable management of the Situtirtamarta tourism destination. Further research may examine psychological factors and perceived destination quality as additional determinants of visitors’ WTP.